Pelatihan Administrasi Sebagai Upaya Peningkatan Tertib Administrasi dan Penguatan Softskill di Lingkungan Organisasi Kemahasiswaan FTIK UIN K.H. Abdurrahman Wahid Pekalongan - Rohman, Akhmad Dalil (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Administrative training in student organizations has an important role in improving administrative order and strengthening student soft skills. This study aims to analyze the effectiveness of text training in the context of student organizations at UIN K.H. Abdurrahman Wahid Pekalongan. The background of this research is the need to improve the quality of administration and develop student soft skills in student organizations. The method of conducting this research includes the stages of training assistance, designing training programs, implementing training, and evaluating training results. The training program is designed to cover administrative skills, which include time management, document management, effective communication, and problem solving. Based on the results of the research, it can be interpreted that administrative training is effective in creating administrative order and strengthening student soft skills in student organizations at UIN K.H. Abdurrahman Wahid Pekalongan. This training makes a significant contribution to improving students' physical skills and soft skill development. Suggestions for further research include involving a control group to compare the effectiveness of the training with the group that did not receive training.